Impact of the Physical Activity Level of Master Athletes on Divided Attention and Binding Processes in Episodic Memory: A Virtual Reality Study. - Maurisse, Indra Nina; Piolino, Pascale; Nouvel, Lucile; Orriols, Eric; Bellegarde, Alexandre; Chikhi, Samy; Largant, Bastien; Lepers, Romuald; Blanchet, Sophie (Experimental Aging Research)
Master athletes are a model of successful aging as their high level of physical activity limits the age-related change of physiological functions. This model is used to investigate how a high level of physical activity impacts cognitive functioning. We aim to study the effect of a high level of physical activity on the ability to manage interferences and binding processes in episodic encoding in an ecological situation. Fifty-five participants were recruited and separated into three groups: 18 master athletes (MA, M = 69.39, SD = 1.13 years), 18 young adults (YA, M = 22.44, SD = 1.10 years), and 19 older adults with a moderate level of physical activity (OA, M = 72.11, SD = 1.10 years). Participants performed an episodic memory task assessing binding processes by encoding under either full or divided attention using a virtual reality technique. After encoding under divided attention, MA outperformed OA in the interference task as well as in the binding score on both free and cued recall. After encoding under full attention, YA and MA did not differ in the number of events recalled in cued recall. Furthermore, significant correlations were found between weekly volume of physical activity and cognitive performance. Binding and interference management, and probably the hippocampus along with prefrontal areas, benefit the most from a sustained and regular physical activity in master athletes.